2008
DOI: 10.1158/0008-5472.can-07-3169
|View full text |Cite
|
Sign up to set email alerts
|

Repression of B-Cell Linker (BLNK) and B-Cell Adaptor for Phosphoinositide 3-Kinase (BCAP) Is Important for Lymphocyte Transformation by Rel Proteins

Abstract: Persistent Rel/nuclear factor-KB (NF-KB) activity is a hallmark of many human cancers, and the Rel proteins are implicated in leukemia/lymphomagenesis but the mechanism is not fully understood. Microarray analysis to identify transformationimpacting genes regulated by NF-KB's oncogenic v-Rel and c-Rel proteins uncovered that Rel protein expression leads to transcriptional repression of key B-cell receptor (BCR) components and signaling molecules like B-cell linker (BLNK), the B-cell adaptor for phosphoinositid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 62 publications
(82 reference statements)
1
22
0
Order By: Relevance
“…However, as previous studies suggest that TNFRSF14 aberrations may confer a poor prognosis in patients treated with chemoimmunotherapy, 4 it is likely that additional or alternative HVEM-mediated mechanisms impact on FL B-cell survival in the autologous setting. As BTLA is also expressed on B cells, and negatively regulates B-lymphocyte transformation and malignant B-cell survival, [35][36][37] reduction of HVEM ligation of BTLA on FL B cells either in cis or trans (from neighboring tumor cells) could potentiate tumor growth and survival in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, as previous studies suggest that TNFRSF14 aberrations may confer a poor prognosis in patients treated with chemoimmunotherapy, 4 it is likely that additional or alternative HVEM-mediated mechanisms impact on FL B-cell survival in the autologous setting. As BTLA is also expressed on B cells, and negatively regulates B-lymphocyte transformation and malignant B-cell survival, [35][36][37] reduction of HVEM ligation of BTLA on FL B cells either in cis or trans (from neighboring tumor cells) could potentiate tumor growth and survival in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…D, Western blots for PU.1, CD10, and ␤-tubulin were compared in BJAB cells expressing an shRNA directed against PU.1 or a scrambled shRNA (con) that does not recognize any human sequence (negative control). E, whole cell extracts were made from DT40 and DT40-v-Rel cells (18), and anti-v-Rel Western blotting was performed (left panel); a v-Rel-transformed chicken spleen cell line served as the positive control. In the right panel, PU.1 and GAPDH transcript levels were analyzed by RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture, DNA Constructs, and Stable Cell Line Generation-Human A293, A293T, Bosc23, BJAB, SUDHL-4, BL41, Daudi, IB4, RC-K8, and chicken DT40 cells (gift of Cé-line Gélinas) (18), were grown in Dulbecco's modified Eagle's medium (DMEM) (Invitrogen) supplemented with either 10 or 20% heat-inactivated fetal bovine serum (FBS) (Biologos) as described (19). The six human B-lymphoma cell lines used in this study are as follows: BJAB, EBV-negative, GCB-like DLBCL (20,21); SUDHL-4, a B-lymphoma that has been characterized as both a follicular lymophoma (22) and GCBlike DLBCL (23); BL-41, EBV-negative Burkitt lymphoma (14); Daudi, EBV-positive, LMP1-negative Burkitt lymphoma (24); IB4, EBV-transformed lymphoblastoid cell line (14); and RC-K8, ABC-like DLBCL (25).…”
Section: Methodsmentioning
confidence: 99%
“…While RelA failed to transform chicken lymphoid cells on its own, replacement of RelA's TAD with that of either v-Rel or c-Rel conferred a strong transforming phenotype both in vitro and in vivo (13). Recent work showed that in addition to activating expression of antiapoptotic and proproliferative genes, the Rel TADs can also lead to gene-specific transcriptional repression of genes such as those for SH3BGRL and the B-cell receptor signaling molecules BCAP and BLNK, and this activity is as important for lymphocyte transformation by v-Rel as is its transactivation function (19,35). Additionally v-Rel can promote expression and alternative splicing of telomerase reverse transcriptase (TERT), which is also involved in lymphocyte transformation (24).…”
mentioning
confidence: 99%
“…The 293T human embryonic kidney cell line, primary chicken embryo fibroblasts (CEFs), v-Rel-transformed chicken spleen cells (CSC), and the DT40 chicken pre-B-cell line were cultured as described previously (12,19). Luciferase assays were performed with extracts from 293T cells (1 ϫ 10 6 ) transfected with calcium phosphate using a total of 6.01 g DNA, including 0.01 g of hRL-null Renilla luciferase DNA as a control, as described previously (12).…”
mentioning
confidence: 99%